Дулаалгын тунгалаг системүүд - С. Баяннасан (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract: In a southerly oriented facade, a Transparent Thermal Insulation (TI) converts incoming solar radiation into usable heat which can be transported to the interior of the building. Transparent insulations are generally installed in front of massive building walls wich serve as energy storage. Different variations of installations have been simulated with a computer program. Real weather data from the Test Reference Year for Ulaanbaatar, Mongolia have been taken into account, a heat gain of as high as 175,8 kWh/m2 seems attainable in wintertime.